Evaluating the labour productivity of social enterprises in comparison to SMEs in Australia. Issue 2 (11th February 2019) - Abbott, Malcolm; Barraket, Jo; Castellas, Erin I-Ping; Hiruy, Kiros; Suchowerska, Roksolana; Ward-Christie, Libby
Abstract : Purpose: The social economy – including not-for-profits, cooperatives, mutual organisations and social enterprises – is playing a stronger role than ever in the delivery of public policy. Yet, these organisations are often anecdotally viewed as relatively inefficient providers. The purpose of this paper is to compare the profitability and labour productivity of social enterprises in the State of Victoria in Australia with that of small- and medium-sized business enterprises (SMEs) in the same state. This paper found that, although social enterprises generally generated smaller profits and, therefore, could be less profitable, their relative level of labour productivity (value added and income to labour employed) was comparable or higher than that of SMEs. This paper responds to the need for comparative insights about social enterprise performance and considers the implications of these findings for new public governance. Design/methodology/approach: The social economy – including not-for-profits, cooperatives, mutual organisations and social enterprises – is playing a stronger role than ever in the delivery of public policy. Yet these organisations are often anecdotally viewed as relatively inefficient providers. Findings: This paper found that, although social enterprises generally generated smaller profits and, therefore, could be less profitable, their relative level of labour productivity (value added and income to labour employed) was comparable or higher than that of SMEs. This paper responds to the need for comparative insights about social enterprise performance and considers the implications of these findings for new public governance. Originality/value: This is the first work that has been done of this sort that has looked specifically at Australia circumstances.